Mentorship in Higher Education: a Concept, a Model and Development Prospects - E. G. Gindes; I. A. Troyan; L. A. Kravchenko (Высшее образование в России)
The article examines the mentorship development in higher education. The need for a scientific reconsideration of the conceptual framework of mentorship in modern conditions, as well as its important practical significance for adapting students, improving the quality of education and professional activity are forming the relevance of this topic. The purpose of the article is to develop the concept of mentorship, to design a model and to plan the mentoring in higher education. An interdisciplinary approach was used to determine the essence of mentorship (consideration of the category in Psychology and Sociology, Pedagogy, Management), a model of mentorship in higher education has been developed with a structural-system analysis, as well as with graphical and statistical methods. The scientific novelty of the article is the development of the conceptual framework of mentoring and applied aspects of its implementation in higher education in Russia. The essential elements of mentorship were identified and considered, namely: the concept and approaches, purpose and objectives, principles and functions. The types of mentorship in higher education were classified according to key criteria: the number of mentees, formalization, period of interaction, method of implementation, direction of interaction, purpose. The main principles of mentoring in higher education are specified. A model of mentoring in higher education was proposed. A systematic analysis of successful practices and mentoring programs in higher education in Russia was carried out. The problems and prospects for mentorship development in modern conditions were identified. The practical significance of the study lies in the possibility of using conceptual developments in the formation and development of the legal framework for the implementation of mentoring, as well as the development and implementation of a mentoring model in higher education institutions.